Is blood type really a risk factor for epistaxis? - (:unkn) unknown (ROYAL BELGIAN SOC EAR, NOSE, THROAT, HEAD & NECK SURGERY, 2016)
Objectives: To determine the association between ABO blood type and epistaxis. Methods: This retrospective study involved 359 patients with idiopathic epistaxis. Patients with risk factors for bleeding, including anticoagulant use, thrombocytopenia, hypertension, liver diseases, elevated bleeding time, low coagulation factor levels, or any benign/malignant tumor, were excluded from the study. Thus, only patients with idiopathic epistaxis were included in this study. For the control group, blood-type information was retrieved from the database of the Turkish Red Crescent, the largest blood bank in Turkey. Results: The distributions of blood types A, B, AB, and O were compared between the epistaxis and control groups. The distribution of blood types A and AB did not significantly differ between the epistaxis and control groups (P> 0.05). Blood type B occurred significantly less frequently (P < 0.05) and blood type O occurred significantly more frequently (P <0.001) in the epistaxis group than in the control group. Conclusions: Our study indicates that in the Turkish population, the O blood type is over-represented in patients with idiopathic epistaxis versus the general population. We conclude that blood type O is a risk factor for idiopathic epistaxis in the Turkish population.
Keywords: Epistaxis; idiopathic; O blood group; risk factor; Turkish population; VON-WILLEBRAND-FACTOR; ABO LOCUS; ASSOCIATION; DIAGNOSIS; STROKE